Perancangan bebedilan karet sebagai media edukasi dan pelestarian Budaya Sunda - Bintang Nugraha; Siwi Anjar Sari; Ahmad Riyadi Swandhani (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
The shift in children's play patterns due to the advancement of digital technology has caused traditional games such as kaulinan barudak to become increasingly marginalized. One of the games that is beginning to fade is bebedilan karet, a rubber-based shooting game that holds both cultural and educational value. This study aims to redesign bebedilan karet so that it can function as an educational medium as well as a means of preserving Sundanese culture. The design approach used is design thinking with the double diamond model, which consists of the stages of emphatize, define, ideate, prototyping, and testing. Data were collected through observation, interviews, and literature studies, then synthesized into a focused design direction. The development process was carried out using the SCAMPER method, supported by the creation of 3D models and physical prototypes based on a modular system. Field testing showed that the product is visually appealing, educational, and capable of enhancing cultural interaction in educational tourism environments. A focus group discussion (FGD) with tourism managers also supported the product's implementation as a permanent educational installation. Thus, this design not only revitalizes traditional games but also offers a design approach that is relevant, adaptive, and meaningful for today’s generation.